Why do community members support clientelistic deals? How collective voting decisions are taken in Uru Indigenous communities, Bolivia - Aline-Sophia Hirseland (German Institute of Global and Area Studies (GIGA), 2024)
This article explores the practice of "instructed voting" prevalent among rural Indigenous communities in Bolivia, referring to the taking of collective electoral decisions. It adds to the debate on clientelistic bloc voting by revealing voters' motives for participating in clientelistic deals, as based on interviews with Uru Indigenous community members and politicians. It shows the ambivalent significance of the practice for the Indigenous communities under study, being a protective mechanism against external threats on the one hand and a gateway to vote buying on the other. Social norms and trust in community authorities are found to be central drivers for achieving voters' compliance. The article adds another piece to the puzzle on how clientelistic deals happen in democratic systems under a secret ballot yet without apparent infringements of the law, which is the case in the communities under study here.
Keywords: 300; Bolivia; clientelism; bloc voting; collective voting decisions; Indigenous peoples